The Creation of Electronic Books to Encourage Biological Literacy - Arrum Ardila Faros; Supriyatin; Ratna Komala (Jurnal Penelitian Pendidikan IPA, 2025)
Biological literacy is essential for students to understand and apply biological concepts. This study aims to develop an e-book on the ecosystem and examine its effect on the biological literacy of Grade X students at SMA Muhammadiyah 4 Jakarta. The research adopted the Hannafin & Peck development model. Based on the needs analysis, students require learning media that is portable and visually engaging. The created e-book has instructional texts that cover four areas of biological literacy: nominal, functional, conceptual, and procedural. It also has AKM-style questions that require reasoning and structured practice exercises. Feasibility testing covered aspects of construction, material, and language, with an average score of 3.4 in the valid category. The effectiveness test showed an increase in students’ biological literacy, with pre-test and post-test average scores of 50.05 and 80.11, respectively. The N-gain score was 0.62 (categorized as medium), and the effect size was 2.98 (categorized as a strong effect). Although effective, the e-book has limitations, such as the inability to complete quizzes directly within the e-book and the requirement of an internet connection to access external practice features. These limitations are recommended to be addressed in future research and development.